High‐Intensity Interval Training Mitigates Sarcopenia and Suppresses the Myoblast Senescence Regulator EEF1E1 - Yaoshan Dun; Wenliang Zhang; Yang Du; Kangling Xie; Yuan Liu; Cui Li; Ling Qiu; Siqian Fu; Thomas P. Olson; Yuqiong Long; Baiyang You; Suixin Liu (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background The optimal exercise regimen for alleviating sarcopenia remains uncertain. This study aimed to investigate the efficacy of high‐intensity interval training (HIIT) over moderate‐intensity continuous training (MICT) in ameliorating sarcopenia. Methods We conducted a randomized crossover trial to evaluate plasma proteomic reactions to acute HIIT (four 4‐min high‐intensity intervals at 70% maximal capacity alternating with 4 min at 30%) versus MICT (constant 50% maximal capacity) in inactive adults. We explored the relationship between a HIIT‐specific protein relative to MICT, identified via comparative proteomic analysis, eukaryotic translation elongation factor 1 epsilon 1 (EEF1E1) and sarcopenia in a paired case–control study of elderly individuals (aged over 65). Young (3 months old) and aged (20 months old) mice were randomized to sedentary, HIIT and MICT groups (five sessions/week for 4 weeks; n = 8 for each group). Measurements included skeletal muscle index, hand grip strength, expression of atrophic markers Atrogin1 and MuRF1 and differentiation markers MyoD, myogenin and MyHC‐II via western blotting. We examined the impact of EEF1E1 siRNA and recombinant protein on D‐galactose‐induced myoblast senescence, measuring senescence‐associated β‐galactosidase and markers like p21 and p53. Results The crossover trial, including 10 sedentary adults (32 years old, IQR 31–32) demonstrated significant alterations in the abundance of 21 plasma proteins after HIIT compared with MICT. In the paired case–control study of 84 older adults (84 years old, IQR 69–81; 52% female), EEF1E1 was significantly increased in those with sarcopenia compared to those without (14.68 [95%CI, 2.02–27.34] pg/mL, p = 0.03) and was associated with skeletal muscle index (R2 = 0.51, p < 0.001) and hand grip strength (R2 = 0.54, p < 0.001). In the preclinical study, aged mice exhibited higher EEF1E1 mRNA and protein levels in skeletal muscle compared to young mice, accompanied by a lower muscle mass and strength, increased cellular senescence and protein degradation markers and reduced muscle differentiation efficiency (all p < 0.05). HIIT reduced EEF1E1 expression and mitigated age‐related muscle decline and atrophy in aged mice more effectively than MICT. Notably, EEF1E1 downregulation via siRNA significantly counteracted D‐galactose‐induced myoblast senescence as evidenced by reduced markers of muscle protein degradation and improved muscle differentiation efficiency (all p < 0.05). Conversely, treatments that increased EEF1E1 levels accelerated the senescence process (p < 0.05). Further exploration indicated that the decrease in EEF1E1 was associated with increased SIRT1 level and enhanced autophagy. Conclusions This study highlights the potential of HIIT as a promising approach to prevent and treat sarcopenia while also highlighting EEF1E1 as a potential intervention target.